The Role of Kashgarrubabi Performance Practice in Teaching the Subject "Instrumental Performance and Ensemble" In Higher Education Institutions - Boychayeva Nazbuvi Avazovna (International Journal on Integrated Education, 2021)
It is known from historical sources that the art of music performance has existed since time immemorial and has come a long way in its development, reaching its present perfect form. Several written sources contain valuable information about music, musical instruments, their unique features, performing arts, as well as master musicians for thousands of years. The author describes in detail the role of the practice of performing Kashgarrubab in the class "Instrumental performance and ensemble" of higher education institutions.